2011
DOI: 10.2106/jbjs.i.01589
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of Cementless Femoral Stems at the Mid-Stem Junction in Modular Revision Hip Arthroplasty Systems

Abstract: We concluded that the stem failure was initiated by a fretting fatigue mechanism and was propagated by a pure bending fatigue mechanism. Risk factors for fractures of the modular junction include excessive body weight and inadequate proximal osseous support because of trochanteric osteotomy, reduced preoperative bone stock, osteolysis, loosening, and/or implant undersizing. Surgeons should consider the use of implants with strengthened junctions when using modular stems in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
121
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(127 citation statements)
references
References 21 publications
2
121
0
2
Order By: Relevance
“…The literature is lacking midterm followup of these TFMT stems currently being used for revision hip arthroplasty. There seems to be concern over the potential long-term failure of these TFMT implants over time, especially dealing with the issue of implant fracture at the level of the modular junction [19,27,32]. In the context of poor proximal femoral bony support around the modular junction, these concerns seem to be further warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature is lacking midterm followup of these TFMT stems currently being used for revision hip arthroplasty. There seems to be concern over the potential long-term failure of these TFMT implants over time, especially dealing with the issue of implant fracture at the level of the modular junction [19,27,32]. In the context of poor proximal femoral bony support around the modular junction, these concerns seem to be further warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown a risk of implant fracture at the level of the modular junction [19,27,32] (Table 1). Concern seems to be heightened where there is poor proximal femoral bony support around the modular junction.…”
Section: Introductionmentioning
confidence: 96%
“…The optimal stem design in these patients is unknown. A number of studies have reported that modular prostheses such as the S-ROM (DePuy, Inc) can help deal with these anatomical challenges [2,5,6,11,19,30]; however, a theoretical disadvantage includes the potential for metal corrosion with modularity [9,20]. The Wagner Cone stem can accommodate small or deformed femora because of its proximal conical, tapered design.…”
Section: Discussionmentioning
confidence: 99%
“…Early to midterm results of modular tapered stems used for femoral revision are now being published [5,6,[11][12][13][14][15][16][17][18]. One study documented success in achieving implant stability and osteointegration, as well as restoring leg length and offset across all Paprosky classifications [15].…”
Section: Discussionmentioning
confidence: 99%
“…Cortical deficiency extending to between lesser trochanter and isthmus the modular junction are reported in the literature on multiple stem designs [3][4][5][6][7]. Manufacturers have developed methods for strengthening the taper junction.…”
Section: Cmentioning
confidence: 99%